The Use of Alkaliphilic Bacteria-based Repair Solution for Porous Network Concrete Healing Mechanism. (2017) - Sangadji, Senot; Wiktor, Virginie; Jonkers, Henk; Schlangen, Erik
Abstract: Bacteria induced calcium carbonate precipitation based on metabolic conversion of nutrients has been acknowledged for having potentials in self-healing cement-based materials. Recent studies have shown the development of bacteria-based repair solution (liquid) for concrete surface repair. This article demonstrates the feasible application of the solution as healing agent to be injected into porous network concrete (PNC). This type of concrete has a porous core which can be used as a media to transport healing agents into the fracture zone. The repair capacity of the solution have been assessed by monitoring the bio-mineral precipitation in the porous cylinder cores. The X-ray tomography and permeability tests at certain time interval were carried out before and after injection of the solution. Polished sections were prepared and examined under ESEM after healing period to investigate healing capacity. The healing potential was then tested by injecting the solution into PNC. The injection of tap water and bacteria based solution was performed through porous network until it reached and flew out through the crack which was formed by three-point bending loading. The healing efficiency was measured by water permeability test before and after injection at several time intervals. The specimens injected with bacteria based solution and cured in wet condition showed higher healing efficiency compared to dry cured specimens.